2002
DOI: 10.1016/s0304-3959(01)00457-2
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of pain and depression to cognitive function in rheumatoid arthritis patients

Abstract: The purpose of this study was to assess the hypothesis that pain and depression negatively impact the cognitive functioning of individuals with rheumatoid arthritis (RA). One hundred twenty-one community-dwelling RA patients (ages 34-84) completed a battery of cognitive tasks and multiple measures of pain and depression. Structural equation modeling techniques were used to assess the relative contributions of pain, depression, and age to cognitive performance. Individuals who performed poorly on cognitive task… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
85
3
8

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 132 publications
(101 citation statements)
references
References 24 publications
5
85
3
8
Order By: Relevance
“…The majority of participants (59%-100%) in the studies were women; the mean age ranged from 37.2 to 62.9 years (with the SD ranging 2.0-13.5). The mean education level ranged from 1.8 to 15.1 years across 10 studies, with 2 not having provided details on education (34,36) and 3 having provided only prevalence rates (more than 8 years [23] and fewer than 12 years [30,31]). Of the 15 studies, 3 (30,31,33) stated the prevalence of cognitive impairment (30%, 0%, and 31%, respectively), while some of the other studies only reported reduced test scores (34,40) or impairment rates across individual tests (32) or combined groups' rates (42) ( Table 4 (Table 5).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The majority of participants (59%-100%) in the studies were women; the mean age ranged from 37.2 to 62.9 years (with the SD ranging 2.0-13.5). The mean education level ranged from 1.8 to 15.1 years across 10 studies, with 2 not having provided details on education (34,36) and 3 having provided only prevalence rates (more than 8 years [23] and fewer than 12 years [30,31]). Of the 15 studies, 3 (30,31,33) stated the prevalence of cognitive impairment (30%, 0%, and 31%, respectively), while some of the other studies only reported reduced test scores (34,40) or impairment rates across individual tests (32) or combined groups' rates (42) ( Table 4 (Table 5).…”
Section: Resultsmentioning
confidence: 99%
“…The inclusion, measurement, and severity of clinical variables varied considerably across studies. The following variables were found to be associated with cognitive function: pain (23,29,31,36,38), disease activity (32,33), fatigue (37), medication (prednisone/steroids [31,40] and MTX [30]), biomarkers (interleukin-6, B cells, and T cells) (34,35,40), and cardiovascular disease risk factors (30). A range of assessment tools was used across studies, prohibiting systematic comparison of clinical profile across samples.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations